Relationship of Coca-Cola Brazil and the communities participant of the social projects: (im) possibilities - Lima, Vanessa Sobreira Casali (2014)
Five years ago, Coca-Cola Brasil launched a program named 'Coletivo Project', with the purpose to enjoy an opportunity of increase on the potential consumption power of the low-income pyramid population that lived on the 'favelas'. At the same time, it had the objective to offer to them a social and financial impact, which is a trust on the future, the first job for the young adults’ participant of this program and an increase on their family source of revenues, through salaries. This was possible because through Coletivo Project, Coca-Cola identified the assets they have through its value chain, focusing on its competencies, such as retail, merchandising and logistics to apply them on courses to teach the young people of the communities and, as a result, form them to be able to find their new jobs. Internal indicators followed in a monthly basis by Coca-Cola demonstrated that the communities that had the presence of Coletivos, in comparison to those without Coletivos, had social and financial impacts. The social was the fact that the young formed started to have more confidence on their future and felt with a higher self-stem to apply for and obtain their first job. On the financial aspect, they were benefit through the increasing of their revenues and also their families and Coca-Cola had an increase on sales, when compared to a community without a Coletivo Project installed. This dissertation seeks to identify the current relationship between Coca-Cola and the communities, through the Coletivo Project classes performed on the NGOs located at this places, in order to identify opportunities for improvement the benefits and the impacts (financial and social) on the NGOs, communities and all stakeholders of this project. This dissertation examines this relationship, through presence interviews performed on four NGOs selected, and located on four of the twenty communities, that are participants of the Coletivo Project on Rio de Janeiro city. These interviews performed with the students, representatives and educators of these NGOs. The covered period of the interviews ranges from April 2014 to August 2014. This dissertation draws on first-hand qualitative empirical evidence gathered through extensive fieldwork. The main findings among possibilities for improvement by Coca-Cola are: • Implement new courses, beyond those existent at Coca-Cola (Retail, Logistics, etc.). • Increase the content of the employment module of Coletivo classes, focusing on improving educational, cultural, economic, political, social and professional life. • Increase the scale, through the quantity of positions on the Retail Coletivo classes. • Develop cultural and sports events with the communities. • Support the points of sales, participant of the practical classes of the Coletivo Retail, with refrigerators and furniture with the Coca-Cola logo. • Provide coffee breaks and meals during the Coletivo classes, using Coca-Cola beverages and partners for food items, developing the nutrition platform of the company and filling a need of the students. • Perform a research with all stakeholders related to this Project, including those students and mothers that are not participant of the Coletivo, in order to listen to them, understand their needs, and offer solutions to fulfill these gaps. and on the side of the • Perform partnerships with educational institutions to make viable other type of courses, more technical, but that have a relation with the core business of Coca-Cola Brasil, such as marketing. • Implement the Coca-Cola University, already existed at the Company. • Create courses or activities focused on the children. Regarding the impossibilities, the findings are: • Improve the basic sanitation of the communities. • Improve the safety on the communities. • Provide a home to those do not have. • Implement courses that have no relationship with Coca-Cola business and expertise, such as gastronomy. However, Coca-Cola can influence stakeholders on that. The results suggest to executives of Coca-Cola that a deep and a qualitative research on the communities of Brazil, in order to listen young people, educators, mothers, partners that offer jobs, from Coletivo and out of the project, is mandatory, to understand their needs, dreams, complains and offer valuable solutions to all.